The relationship between spirituality and self-efficacy among trainee counselors at the Universiti Putra Malaysia - Subarimaniam, Neerushah; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This research involves the study of spirituality and self-efficacy in dealing with legal and ethical issues. Value such as spirituality is viewed and accepted as an important aspect in enhancing various dimensions of counseling practices. Spirituality is a person’s search for purpose and meaning of life which involves transcendence, self-transcendence, and a personal connection with the highest power. While self-efficacy is defined as an individual’s beliefs regarding his or her ability to accomplish a task successfully. The spiritual experience of a counselor enables him or her to positively affect the growth of client. This shows the tendency of client to cooperate with counselor during the time of ethical dilemma. Spirituality can also be best seen in the context of belief system, which can affect one’s self-efficacy in dealing with ethical dilemmas. In short, counselors will be capable of addressing ethical and legal issues with high self-efficacy if they have more spiritual knowledge and experiences. The purpose of this study is to examine the relationship between spirituality and counselor’s self-efficacy in dealing with ethical issues. The respondents will be trainee counselors who will need to answer a set of questionnaires consisting of three components: a) demographic background; b) perceived spirituality; and c) self-efficacy in dealing with legal and ethical issues. This study will use descriptive statistics to provide basic information retrieved from the data as well as Pearson Correlation to examine the relationship between spirituality and self-efficacy of counselors in dealing with ethical issues.